The music workforce, cultural heritage and sustainability - Petocz, P.; Reid, A.; Bennett, Dawn (Institute of Creative Idustries Design, 2014)
Larger than any other creative industry, music is an intangible cultural asset whose sustainability is included in the United Nation’s fourth pillar of sustainability. Music contributes to both cultural heritage and also cultural sustainability. Despite this, not enough is known about the characteristics and dynamics of work and career for musicians or the relationships between these activities and cultural life. While there is some recent research describing the use of music for cultural heritage and sustainability in contemporary indigenous contexts, little of this describes the importance of music for culture in urbanized communities. Writing from the perspective of Australia, we contend that the idea of ‘creolization’ – the development of a new culture from a combination of traditional ones – is a useful concept for broadening understanding of music for cultural heritage and sustainability. More practically, we argue that exploring musical artifacts and performance practices from different cultures and times can contribute to our understanding of cultural heritage and highlight cultural sustainability as an essential professional disposition.